2009
DOI: 10.1007/s00535-008-2292-4
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon endoscopy: past, present, and future

Abstract: Double-balloon endoscopy (DBE) was developed as a new technique for visualization of and intervention in the entire small intestine. In DBE, the intestinal walls are held apart by a balloon attached to the distal end of a soft overtube. DBE has been reported worldwide to be very useful for not only diagnosis but also endoscopic therapy. Biopsy samples of small intestinal tumors can be obtained using DBE, and the appropriate treatment can be selected before a surgical procedure. For inflammatory diseases, DBE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…Endoscopic therapy in the small intestine, whose wall is very thin, should be performed with special care to avoid complications such as bleeding and perforation [63] .…”
Section: Ioementioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic therapy in the small intestine, whose wall is very thin, should be performed with special care to avoid complications such as bleeding and perforation [63] .…”
Section: Ioementioning
confidence: 99%
“…DBE and video capsule enteroscopy have changed this approach and it is now possible to not only to perform endoscopic surveillance and diagnose these lesions, but also to resect them [37,58,73,77,78] . Many reports on DBE have suggested that this new method may be able to replace at least IOE in many circumstances [63,79,80] . Indications of IOE have diminished over recent years because of the development of DBE [57] .…”
Section: Overall Experience Of Pjs Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the serious problem of NSAIDs-induced small intestinal damage has become a topic of great interest to gastroenterologists, since video capsule endoscopy (VCE) and balloon enteroscopy (BE) are available for the detection of small intestinal lesions [2][3][4]. Such lesions have been of great concern in clinical settings, and their treatment and prevention must be devised as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, mechanical stress on the pancreas seems to be presumable. Traumatic injury of the pancreas seems to be the main cause of acute pancreatitis (14,41,44,59,64).…”
Section: Figmentioning
confidence: 99%